New Insights into the Structure and Reactivity of Uracil Derivatives in Different SolventsA Computational Study - Islam, Shahidul M; Ibnat, Zahin (ACS omega, 2020)
Ab initio calculations were carried out to understand the reactivity and stability of some uracil derivatives, cytosine, 1-methyl cytosine, and cytidine in solvents, water, dimethyl sulfoxide (DMSO), n-octanol, and chloroform. Geometries were fully optimized at MP2 and B3LYP using the 6-31+G(d,p) basis set by applying the Solvation Model on Density (SMD) in solvent systems. The syn conformer of cytidine (cytidine II) is the most stable conformer in the gas phase, while the anticonformer (cytidine IV) is most stable in all of the solvents. Solvation free energy and polarizability values in different solvents decrease in the order water > DMSO > n-octanol > chloroform, while dipole moment, first-order hyperpolarizability, and HOMO–LUMO energy gap values follow the order of polar protic solvent (water and n-octanol) > polar aprotic solvent (DMSO) > nonpolar solvent (chloroform). The solvation free energy, dipole moment, polarizability, and first-order hyperpolarizability values also follow the order of cytosine > 1-methyl cytosine > cytidine. To illustrate that the molecular properties correlate well with the reactivity of the molecules, ab initio calculations were carried out for the reaction of uracil derivatives with Br2 in the gas phase, water, DMSO, n-octanol, and chloroform. All ground and transition state geometries were fully optimized at B3LYP/6-31+G(d,p), and energies were also calculated at G3MP2 for cytosine and 1-methyl cytosine. For cytosine and 1-methyl cytosine, Gibbs energies of activation decrease with the polarity of the solvent that is chloroform > n-octanol > DMSO > water, while the Gibbs energies of activation for the reaction with cytidine decrease in the order of water > DMSO > n-octanol > chloroform. These results suggest that solvent polarity is very important for the stability and reactivity of uracil derivatives. Hydrogen bonding may also play an important role mainly for cytidine. Free energies of activation decrease with the size of the molecule, i.e., cytosine > 1-methyl cytosine > cytidine.